Roles and Responsibilities in Accurate Job Orientation - Isotalo, Anni (My University, 2012)
Job orientation for newcomers is an important phase with far reaching consequences. By completing the orientation fully, a newcomer can sooner work by themselves and with better profits. Orientation process involves several persons with different roles and responsibilities. The object of this study is to figure out how the roles and responsibilities are fulfilled during the orientation process between newcomer, supervisor and the HR department in an international organization. Literature review handles orientation as a part of human resource management (HRM). The term orientation is defined and all the related parties are described. There are many activities and situations related to the orientation process. These are taken into account when handling the orientation process. One significant part of orientation is socialization, which is informally related to the work environment and social network. The empirical part of the research is made using the qualitative method. The data was collected in 13 semi-structured live interviews in Finnish and English from managers and subordinates who were working in an assignment organization. The interviewees were from 2 different countries and represented 3 different departments. The managers’ average work experience in a managerial position in the company was 14 years. Subordinates’ average work experience in the company was 8,6 months. The findings of the thesis reveal that supervisors are the persons with most responsibilities in the orientation process. Although they were using an induction plan guide provided by the HR department, but the awareness of it was slight. It appeared that the managers were missing support from the HR department, when it came to their practical issues. Business units were took responsibility of the orientation and their roles were conspicuous. Altogether newcomers were satisfied with orientation as a whole. Development ideas were mainly related on the timing and information sharing across the border. Research results closely reflected the selected theory.
Keywords: job orientation; socialization; newcomer; situational leadership; fi=Johtaminen ja organisaatiot|en=Management and Organization|